2013
DOI: 10.1103/physrevd.87.044006
|View full text |Cite|
|
Sign up to set email alerts
|

Towards experimentally testing the paradox of black hole information loss

Abstract: Information about the collapsed matter in a black hole will be lost if Hawking radiations are truly thermal. Recent studies discover that information can be transmitted from a black hole by Hawking radiations, due to their spectrum deviating from exact thermality when back reaction is considered. In this paper, we focus on the spectroscopic features of Hawking radiation from a Schwarzschild black hole, contrasting the differences between the nonthermal and thermal spectra. Of great interest, we find that the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…With the relatively low energy scale for quantum gravity and the large dimensions, the production of micro black holes and the observation of Hawking radiations has already been studied [55][56][57][58][59][60]. If Hawking radiations from a micro black hole were observed in an LHC experiment, our results show that it can definitely determine whether the emission spectrum is indeed non-thermal [54] or not. Thus it provides an avenue towards experimentally testing the long-standing "information loss paradox".…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…With the relatively low energy scale for quantum gravity and the large dimensions, the production of micro black holes and the observation of Hawking radiations has already been studied [55][56][57][58][59][60]. If Hawking radiations from a micro black hole were observed in an LHC experiment, our results show that it can definitely determine whether the emission spectrum is indeed non-thermal [54] or not. Thus it provides an avenue towards experimentally testing the long-standing "information loss paradox".…”
Section: Discussionmentioning
confidence: 75%
“…Although the derivation of the non-thermal spectrum is based on solid physics, it remains to be confirmed experimentally or in observations. A recent analysis by us [54] show that the non-thermal spectrum can indeed be distinguished from the thermal spectrum by counting the energy covariances of Hawking radiations. The energy covariances actually measure the correlation among Hawking radiations.…”
Section: Discussionmentioning
confidence: 99%
“…With the relatively low energy scale for quantum gravity and the large dimensions, the production of micro black holes and the corresponding observation of Hawking radiations has already been studied [27][28][29][30][31][32]. If Hawking radiations from a micro black hole were observed in an LHC experiment, our results show that it can definitely determine whether the emission spectrum is indeed non-thermal [26] or not. Thus it provides an avenue towards experimentally testing the long-standing "information loss paradox".…”
mentioning
confidence: 72%
“…Although the derivation of the non-thermal spectrum is based on solid physics, it remains to be confirmed experimentally or in observations. A recent analysis by us show that the nonthermal spectrum can be distinguished from the thermal spectrum by counting the energy covariances of Hawking radiations [26]. With the relatively low energy scale for quantum gravity and the large dimensions, the production of micro black holes and the corresponding observation of Hawking radiations has already been studied [27][28][29][30][31][32].…”
mentioning
confidence: 99%
“…From the geometric side, when a geodesic motion is considered, to an observer or detector at the south pole at r = 0, the horizon location at r = r H and the coordinate time η = ∞ are not well-defined and are usually defined only as a limiting process. Recent study indicated that at least for black holes, when a probe passes through the horizon, the location of the horizon is actually not fixed but changes [27] and this will be the key for accounting for the information conservation as demonstrated in a series of publications [28,29,30,31,32,33]. Related considerations in spirit have also been given very recently 3 We will confine ourselves in this paper to this classical discussion, not touching the subtle g s → 0…”
Section: Geometric Tachyon On the Causal Static Patchmentioning
confidence: 89%